Importance of local and landscape variables on multiple facets of stream fish biodiversity in a Neotropical agroecosystem - Roa-Fuentes, Camilo A. [UNESP]; Heino, Jani; Zeni, Jaquelini O. [UNESP]; Ferraz, Silvio; Cianciaruso, Marcus V.; Casatti, Lilian [UNESP] (Springer Nature, 2020)
Few studies have considered the effects of environmental variables at different spatial scales on Neotropical stream biodiversity. Furthermore, scale-related studies mostly include only one facet of biodiversity. To determine the contribution of local and landscape variables to the variation in the taxonomic, functional and phylogenetic α-diversity of stream fish assemblages, we sampled 85 streams in the Upper Paraná River basin, Brazil. Local variables explained a substantial fraction of the variance in almost all biodiversity facets. Landscape variables (i.e., land-use and spatial variables) contributed little to the variation in the α-component of biodiversity. Our results thus highlight the importance of local features for maintaining stream fish biodiversity in agroecosystems. Probably, land-use were not significant because the study area was in a relatively homogeneous landscape severely impacted by anthropogenic activities. It is possible that insignificant effects of spatial structuring occurred because the ichthyofauna has already gone through a homogenization process and/or due to the spatial scale of our study. We suggest that even though local-scale restoration actions would influence biodiversity, we should not neglect landscape restoration because substantial improvements in the ecological integrity of streams are more likely to be accomplished with large-scale actions (e.g., re-establishment of the native riparian forest).
Keywords: Functional diversity; Pasture; Phylogenetic diversity; Stream restoration; Sugarcane; Taxonomic diversity